Experimental Study on A Pendulum Wave Energy Converter - 邱守强 叶家玮 王冬姣 梁富琳 (China ocean engineering, 2013)
Many of the existing wave energy converters （WEC） are of oscillating water column （OWC） and point absorber （PA） types. Fewer references have been published in public on the pendulum type WEC. A series of experimental tests on a bottom-hinged pendulum WEC model are carded out and some results are revealed in the present study. The purpose of this paper is to present a detailed description of the tests. It is found that wave energy conversion efficiency varies with the applied damping and wave conditions. In addition, special attention is given to the effect of the water ballast on the efficiency of the wave energy converter. It is demonstrated that the ballast plays an important role in energy extraction. Better understanding on how the performance of the device is influenced by damping, wave height, wave period and ballast is shown.